Efforts to Improve Student Learning Outcomes in Mathematics Learning Using Interactive Powerpoint Media at SD Negeri Cucum - Zaitun Munar (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to enhance student learning outcomes in Islamic religious education through the use of interactive PowerPoint presentations. Employing a classroom action research approach, the study follows four stages: planning, action, observation, and reflection. The research subjects were elementary school students, and data were collected using tests to assess learning outcomes and observations to evaluate teacher and student activities during lessons. Descriptive statistical analysis was used to compare the results against predefined success indicators. The findings reveal that interactive PowerPoint significantly improves student performance in Islamic religious education, as evidenced by an increase in learning achievement from 48.71% in the pre-cycle, to 63.39% in the first cycle, and reaching 90.96% in the second cycle. Therefore, interactive PowerPoint proves to be an effective alternative for enhancing learning outcomes in this subject area.